The Development of Mushroom Interactive Student Worksheet Based on Discovery Learning as Teaching Materials for Class X High School Students (Journal of Biology Education, 2023)
The 2013 curriculum requires students to understand various subject matter actively and independently. One of the materials that make it difficult for students to learn is the mushroom material. For this reason, it is necessary to apply a discovery learning model to mushroom material. In addition, the process of learning biology at SMA N 1 Kebumen has not yet utilized technology optimally. The LKPD used is still in printed form and is sourced from textbooks only. So we need an interactive electronic LKPD with varied learning resources. The purpose of this study was to analyze the validity and effectiveness of interactive teaching materials. The research method, namely Research and Development, uses steps to a small scale. The subjects in this study were 15 students taken using the "purposive sampling" technique for class X MIPA D with a ratio of 5:5:5 including students with high:medium:low abilities. The results showed that the validity of the mushroom interactive teaching materials was valid based on the average material validator score of 72.3% and the media validator average of 96.66% the criteria were very valid. Mushroom interactive teaching materials were effectively applied by obtaining a classical completeness score of 93.33% and an average N-gain value of criteria. Teacher responses obtained an average score of 96.66% very positive criteria and student responses obtained an average score of 90.58% very positive criteria. The conclusion of this study is that interactive teaching materials are valid and effective to be used as teaching materials for class X SMA students.